Numerical and Experimental Study on Crushing Properties of Hard Coal Using Impacting-Cutting Technique - Qiang Zhang; Cong Wang; Ying Tian (Shock and Vibration)
The reserves of high-quality coal seams have been greatly reduced in recent years, and the low efficiency of traditional cutting methods in hard coal seams has become a problem for the coal production industry. In order to improve the mining efficiency, an impacting-cutting technique was proposed in this study. A drum modification model with picks impact function was established, and crushing properties of the impacting-cutting drum at f4, f5, and f6 coal hardness were simulated using the discrete element method. The simulation results show that the impacting-cutting drum has higher coal crushing efficiency, lower drum force, and more stable cutting processes than the traditional drum. It shows that hard coal might be effectively reduced by the impacting-cutting technique to reduce the difficulty of mining, and reflected the applicability in hard coal seams. Meanwhile, a simplified test device for the impacting-cutting technique was designed. And the actual coal crushing performance was tested. The test results show that the force of the cutting mechanism in the impact mode is lower than that of the nonimpact mode, and the force is more stable. It proves that the impacting-cutting technique has a higher applicability of hard coal seams than the traditional technique.